New trends in luxury goods consumptions: a cross-cultural analysis. (2019) - Calvelli, Adriana; Cannavale, Chiara; Bassano, Clara; Laurenza, Elena
Luxury is a very subjective concept, strictly connected to the values and assumptions people use to orientate their choices and behaviours. Values are concepts or beliefs, which refer to desirable states or behaviours and are used as standards or criteria to select or evaluate behaviour and events (Schwartz, 1994). They influence individuals' perceptions and choices, and this happens both at an individual and at a collective level. Our study is a working progress paper as a first attempt to investigate the effects of cultural values on the demand of luxury goods, to answer the following questions: Does consumers' perception of luxury goods vary across countries? Does culture affect this perception?